Mutual recognition of national regulations in the EC - Jochen Michaelis (Intereconomics, 1990)
The principle of the mutual recognition of national regulations is often seen as the best course towards the realization of the EC single market, but there still remains great uncertainty concerning the interpretation of this principle. Which companies must observe which regulations? Will there be changes affecting current competitive conditions?
Keywords: 330; European Internal Market